Gastrodin ameliorates the lipopolysaccharide-induced neuroinflammation in mice by downregulating miR-107-3p - Song, Jin-Jin; Li, Hui; Wang, Nan; Zhou, Xiao-Yan; Liu, Yan; Zhang, Zhen; Feng, Qian; Chen, Yu-Ling; Liu, Dan; Liang, Jia; Ma, Xiang-Yu; Wen, Xiang-Ru; et al. (Frontiers in Pharmacology, 2022)
Background: Neuroinflammation plays a pivotal role in the pathogenesis of Central Nervous System (CNS) diseases. The phenolic glucoside gastrodin (GAS), has been known to treat CNS disorders by exerting anti-inflammatory activities. Our aim was to investigate the potential neuroprotective mechanisms of GAS on lipopolysaccharide (LPS)-induced mice. Methods: Male C57BL/6J mice were treated by LPS, before which GAS was adminisrated. The behavior tests such as forced swim test, tail suspension test, and elevated plus maze were performed to evaluate depressive-anxiety-like behaviors. A high-throughput sequencing (HTS) analysis was performed to screen out distinctive miRNAs which were validated using quantitative real-time PCR. Then, miRNA agomir or NC was injected stereotaxically into hippocampus of mice to explore the role of miRNA on GAS in response to LPS. Furthermore, Immunofluorescence and the hematoxylin and eosin (H&E) staining were employed to observe the cellular morphology. The protein levels of pro-inflammatory factors were evaluated by western blot. Finally, the target mRNA of miRNA was predicted using bioinformatics analysis. GO and KEGG enrichment analyses were conducted to clarify the potential function of target protein , which were visualized by bubble charts. Results: The behavioral data showed that mice in the LPS group had obvious depressive-anxiety-like behaviors, and 100 mg/kg GAS could improve these behavioral changes and alleviate the levels of pro-inflammatory cytokines in the hippocampus when mice were exposed to LPS for 6 h. Meanwhile, LPS-induced microglia and astrocyte activation in the CA1, CA2, CA3, and DG regions of the hippocampus were also reversed by GAS. Furthermore, miR-107-3p were screened out and verified for GAS in response to LPS. Importantly, miR-107-3p overexpression negatively abrogated the neuroprotective effects of GAS. Moreover, KPNA1 might be the target molecular of miR-107-3p. KPNA1 might regulate 12 neuroinflammation-related genes, which were mainly involved in cytokine−mediated signaling pathway. Conclusion: These results suggested that GAS might alleviate the LPS-induced neuroinflammation and depressive-anxiety-like behaviors in mice by downregulating miR-107-3p and upregulating the downstream target KPNA1. The indicates miR-107-3p may provide a new strategy for the treatment of CNS diseases.